2014
DOI: 10.1002/app.41771
|View full text |Cite
|
Sign up to set email alerts
|

Self‐nucleation behaviors of olefinic blocky copolymer/montmorillonite nanocomposites with collapsed and intercalated clay layers

Abstract: The self‐nucleation behavior of olefinic blocky copolymer (OBC) / organically modified montmorillonite (OMMT) nanocomposites with a novel collapsed clay structure (c‐OMMT) was studied and compared with that of the nanocomposites with an intercalated clay structure (OBC/i‐OMMT). Their behaviors appear different in three temperature domains, Domain I (DI) in which the polymer is completely melted and only the heterogeneous nuclei are present, Domain II (DII) in which only self‐nucleation occurs and Domain III (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This fact is advantageous for obtaining a composite with improved mechanical strength, thermal stability, barrier properties, and reduced flammability . However, the small displacement of the second peak of the clay, about 8°, d(002), suggests an increase in the spacing between clay layers, an indication that the clay is partially intercalated in the polymer matrix . Therefore, the results show that the nanoclay is in an intercalated/exfoliated configuration in polymeric films.…”
Section: Resultsmentioning
confidence: 90%
“…This fact is advantageous for obtaining a composite with improved mechanical strength, thermal stability, barrier properties, and reduced flammability . However, the small displacement of the second peak of the clay, about 8°, d(002), suggests an increase in the spacing between clay layers, an indication that the clay is partially intercalated in the polymer matrix . Therefore, the results show that the nanoclay is in an intercalated/exfoliated configuration in polymeric films.…”
Section: Resultsmentioning
confidence: 90%
“…14 Zuo et al also investigated the structure evolution during deformation of OBCs at room temperature and compared it with olen random copolymers (ORC); it was found that high 1-octene comonomers in so blocks and low density of non-crystallizable blocks could lead to a less effective network, although they possess similar ethylene-octene composition and overall density. 21,22 However, these approaches can inevitably cause a signicant loss of elasticity. It was reported that the properties are better when processed at temperatures higher than the mesophase separation temperature (TMST).…”
Section: Introductionmentioning
confidence: 99%
“…Similar phenomenon was Table 1 The weight percentage of PCL (W PCL ), number-average molecular weight of PCL (M n ), grafting density of PCL (s), gyration radius (R g ) and distance between the adjacent grafted PCL chains (d) in different samples. observed for the olefinic blocky copolymer/montmorillonite nanocomposites in our previous work [28]. This is probably due to the thermal lag in the heating process, as compared with the annealing process in the SN experiments.…”
Section: Self-nucleation Of Mwcnts-g-pcl-6kmentioning
confidence: 84%